Analysis of the Structure, Conduct and Performance of the Chrysanthemum Flower Market in Pasuruan Regency (Study Case in Tutur Village) - Zakia Putri Sulaiman; Ratya Anindita; Abdul Wahib Muhaimin (HABITAT, 2022)
With a total FOB value of $792,698, chrysanthemums had a strong export performance in the previous four years (2014–2018). This demonstrates that chrysanthemums are very competitive in the global market (Balithi, 2019). When comparing the land area in 2018 to the previous year, 2017, the land area declined to 11,105,178 m2, with a production of 488,176,610 and a productivity of 43.96 per hectare of land in 2017. (BPS, 2019). In this research, the structure, behavior, and performance of the chrysanthemum market were investigated with the help of 25 respondents and 18 merchants, with the SCP technique being applied. The findings revealed that monopolistic institutions were responsible for the market structure, which consisted of perfect competition at the farmer level and a monopoly at the marketing agency level, as well as significant obstacles to entry, product differentiation, and vertical integration. According to the findings of an investigation into the behavior of the chrysanthemum market in Tutur Village, wholesalers and flower shops are the marketing agents who conduct the greatest number of marketing duties. Wholesalers have a monopoly on market information, with farmers serving as price takers and, subsequently, marketing organizations serving as price makers. Farmers' marketing options are constrained as a result of the presence of capital linkages between them and intermediaries, and many choose to sell their products through intermediaries rather than directly to consumers. In Tutur Village, there are four different ways in which chrysanthemums may be sold. As a result of the formation of a market structure, each marketing agent employs methods and colludes with others to achieve success. Following an investigation into market performance in Tutur Village, it has been discovered that channel 4 has the largest overall margin, followed by channel 5.